Practical Approaches and Advances in Spatial Tools to Achieve Multi-Objective Marine Spatial Planning - Lombard, Amanda T.; Ban, Natalie C.; Smith, Joanna L.; Lester, Sarah E.; Sink, Kerry J.; Wood, Spencer A.; Jacob, Aerin L.; Kyriazi, Zacharoula; Tingey, Richard; Sims, Helena E. (Frontiers in Marine Science, 2019)
Marine spatial planning (MSP) processes seek to better manage ocean spaces by balancing ecological, social and economic objectives using public and participatory processes. To meet this challenge, MSP approaches and tools have evolved globally, from local to national scales. At two International Marine Conservation Congresses (2016 and 2018), MSP practitioners and researchers from diverse geographic, technical and socio-economic contexts met to share advances in practical approaches and spatial tools to achieve multi-objective MSP. Here we share the lessons learned and commonalities that emerged from studies conducted in Belize, Canada, South Africa, Seychelles, the United Kingdom and the United States on a number of topics related to advancing MSP. We identify seven important themes that we believe are broadly relevant to any multi-objective MSP process: (1) indigenous and local knowledge should inform planning goals and objectives; (2) transparent and evidence-based approaches can reduce user conflict; (3) simple ecosystem service models and scenarios can facilitate multi-objective planning; (4) trade-off analyses can help balance diverse objectives; (5) ecosystem services may assist planning for high value-data poor Blue Economy sectors; (6) game theoretic decision rules can help to deliver fair, equitable and win–win spatial allocation solutions; and (7) strategic mapping products can facilitate decision making amongst stakeholders from different sectors. Some of these themes are evident in MSP processes that have been completed in the previous decade, but the fast-evolving field of MSP is addressing increasingly more complex objectives, and practitioners need to respond with practical approaches and spatial tools that can address this complexity.